Chitooligosaccharide Biguanidine Alleviates Liver Injury and Insulin Resistance in Type 2 Diabetic Rats. (30th October 2019) - Zhao, Liyan; Zheng, Qifang; Zou, Yalu; Wang, Yuanyuan; Wu, Yuntang; Liu, Xiaofei
Abstract: Chitooligosaccharide biguanidine (COSG) is a derivative of chitooligosaccharide that has been proven to have antidiabetic activity. In this study, the therapeutic effects of COSG on liver injury and insulin resistance are evaluated, and the possible mechanism is explored. Streptozotocin‐induced diabetic rats are treated with COSG for 8 weeks. COSG treatment significantly increases the activity of catalase, superoxide dismutase, and glutathione peroxidase and inhibits the activity of malonic dialdehyde. Histological observation reveals that COSG treatment also alleviates the probability of hepatocyte degeneration or necrosis. Furthermore, COSG treatment significantly activates the insulin receptor substrate‐2/phosphatidylinositol 3 kinase/protein kinase B signaling pathway and increases the glucose transporter 2/glucokinase expressions, which regulates liver glucose conversion and insulin secretion, COSG treatment also inhibits the glucose‐6‐phosphatase/phosphoenolpyruvate carboxykinase activations, resulting in a reduced level of blood glucose. Accordingly, COSG can protect against liver dysfunction caused by type 2 diabetes. Abstract : Chitooligosaccharide biguanidine (COSG) significantly alleviates liver dysfunction in type 2 diabetic rats. In detail, COSG inhibits liver injury through regulating the activities of antioxidant enzymes. Furthermore, COSG relieves insulin resistance through the phosphatidylinositol 3 kinase/protein kinase B signaling pathway, which activates the glucose transporter 2/glucokinase pathway to regulate insulin secretion and inhibits the glucose‐6‐phosphatase/phosphoenolpyruvate carboxykinase pathway to reduce gluconeogenesis.